Evolutionary Game Theory and Linguistic Typology: a Case Study - Jäger, Gerhard (Proceedings of the Amsterdam Colloquium, 2003)
The paper deals with the typology of the case marking of semantic core roles. The competing economy considerations of hearer (disambiguation) and speaker (minimal effort) are formalized in terms of evolutionary game theory. It will be shown that the case marking patterns that are attested in the languages of the world are those that are evolutionary stable for different relative weightings of speaker economy and hearer economy, given the statistical patterns of language use that were extracted from corpora of naturally occurring conversations.